2023
DOI: 10.3389/fpubh.2023.1117923
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' practices and their influencing factors in palliative care

Abstract: BackgroundIn 2017, the Chinese government launched a pilot project in palliative care, in which Shanghai was a pioneer. Nurses play a key role in palliative care services as they are the main providers improving the quality of services for patients and their families. However, little is known about practices and influencing factors in the field of palliative care from a nursing perspective in China. This is an original empirical study that has meticulously analyzed the interrelationship and intensity between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
1
3
0
1
Order By: Relevance
“…The study found that attitude was a mediator between knowledge and self-reported practice among nurses. Consistent with previous research Xu et al, 2023), knowledge has a direct effect on self-reported practice. We believe this would be due to knowledge improving nurses' confidence to practise hospice care.…”
Section: Mean ± Sdsupporting
confidence: 90%
“…The study found that attitude was a mediator between knowledge and self-reported practice among nurses. Consistent with previous research Xu et al, 2023), knowledge has a direct effect on self-reported practice. We believe this would be due to knowledge improving nurses' confidence to practise hospice care.…”
Section: Mean ± Sdsupporting
confidence: 90%
“…Second, as defined by Ajzen and Fishbein (1980) normative beliefs relate to an individual's view of a particular behaviour from a societal perspective. More specifically, it refers to the individual's beliefs that individuals or groups think they should or should not perform the behaviour, such as the RN's colleagues, patients or family members (Xu et al, 2023).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Second, as defined by Ajzen and Fishbein ( 1980 ) normative beliefs relate to an individual's view of a particular behaviour from a societal perspective. More specifically, it refers to the individual's beliefs that individuals or groups think they should or should not perform the behaviour, such as the RN's colleagues, patients or family members (Xu et al, 2023 ). Third, control beliefs encompass an individual's skills and abilities, as well as the facilitators and barriers to actual performance which when taken together, are important determinants of the behaviour (White et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated a broad range of factors influencing PEOL care practice among nurses, including perceived advantages and obstacles, subjective norms, religious beliefs, intention, self-efficacy, skills, knowledge, qualifications, attitudes, experience, education, culture, and age (Alshammari et al, 2023 ; Jeong et al, 2020 ; Soikkeli Jalonen et al, 2020 ; Xu et al, 2023 ). From their studies, Alshammari et al ( 2023 ) and Carvajal et al ( 2019 ) concluded that nurses constantly emphasized the role of support from more experienced colleagues and collaboration with patients’ families in delivering impactful PEOL care.…”
Section: Introductionmentioning
confidence: 99%